Trend 1998 - 2012. International Monetary Fund. Government Finance Statistics: Expenses | Country: Iceland | Government Entity: Central Govt Budgetary Accts | Subject*: Expenditure | CashAccrual: Accrual | Source Organization: , 1998-2012. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 056-003-002. - International Monetary Fund (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
International Monetary Fund (2015). Government Finance Statistics: Expenses | Country: Iceland | Government Entity: Central Govt Budgetary Accts | Subject*: Expenditure | CashAccrual: Accrual | Source Organization: , 1998-2012. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 056-003-002. Dataset: Shows expenditures by government units for each country and selected country groups, by type of expenditure. Where specified, amounts are reported in National Currency (n.c.) units. Presents revenue, expense, transactions in assets and liabilities, and stocks of assets and liabilities of general government and its subsectors as reported by member countries of the International Monetary Fund (IMF). Statistics are from the Government Finance Statistics (GFS) system produced by the IMF, which is designed to provide statistics that enable policymakers and analysts to study developments in the financial operations, financial position, and liquidity situation of the general government sector or the public sector in a consistent and systematic manner. The GFS analytic framework can be used to analyze the operations of a specific level of government and transactions between levels of government as well as the entire general government or public sector. Two types of flows are recorded in the GFS system: transactions and other economic flows, which refer to the creation, transformation, exchange, transfer, or extinction of economic value. The statistical unit employed in the GFS system is the institutional unit, ie, units that affect fiscal policies, and can, in its own right, own assets, incur liabilities, and engage in economic activities and transactions with other entities. Data are typically obtained directly from the accounting records of these entities. Code structure: http://www.imfstatistics.org/imf/GFSCodes.htm Category: Government and Politics, International Relations and Trade Source: International Monetary Fund Headquartered in Washington, DC, the International Monetary Fund (IMF) was conceived at a United Nations conference convened in Bretton Woods, New Hampshire, United States, in July 1944. The 44 governments represented at that conference sought to build a framework for economic cooperation that would avoid a repetition of the vicious circle of competitive devaluations that had contributed to the Great Depression of the 1930s. As of 2012, the IMF has 188 member countries. Its primary purpose is to ensure the stability of the international monetary system, specifically the system of exchange rates and international payments that enables countries (and their citizens) to transact with one other. This system is essential for promoting sustainable economic growth, increasing living standards, and reducing poverty. The Fund’s mandate has recently been clarified and updated to cover the full range of macroeconomic and financial sector issues that bear on global stability. The IMF is a specialized agency of the United Nations but has its own charter, governing structure, and finances. Its members are represented through a quota system broadly based on their relative size in the global economy. http://www.imf.org/ Subject: Public Finance, Government Spending